2007
DOI: 10.1093/bja/aem258
|View full text |Cite
|
Sign up to set email alerts
|

Similarity between the suprasystolic wideband external pulse wave and the first derivative of the intra-arterial pulse wave

Abstract: The suprasystolic WEP signals can be used to derive arterial pressure waves which, although not identical, track changes in the intra-arterial pulse wave induced by vasoactive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…1. At the brachial end, a suprasystolic cuff is applied to almost completely occlude the artery (Payne et al, 2007). In this work, the external pulse is transduced directly from the suprasystolic cuff pressure.…”
Section: Arterial Modelmentioning
confidence: 99%
“…1. At the brachial end, a suprasystolic cuff is applied to almost completely occlude the artery (Payne et al, 2007). In this work, the external pulse is transduced directly from the suprasystolic cuff pressure.…”
Section: Arterial Modelmentioning
confidence: 99%
“…The K1 signal is not affected by the local pulse wave reflection of the arm and hand and is more representative of a central arterial pressure pulse. Payne et al [ 21 ] have demonstrated an intrinsic relationship between the suprasystolic WEP pattern (i.e., K1) and the first derivative of an intra-arterial pressure wave. The K1 pattern has 2 identifiable systolic peaks separated by an identifiable trough.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data indicate that suprasystolic wideband external pulse may be monitored using a broad bandwidth piezoelectric sensor located over the brachial artery under the distal edge of a sphygmomanometer cuff [27]. The corresponding signal closely resembles the first derivative of intraarterial blood pressure both at baseline and following pharmacologically induced blood pressure increases and decreases in healthy volunteers [27].…”
Section: Miscellaneousmentioning
confidence: 93%
“…The corresponding signal closely resembles the first derivative of intraarterial blood pressure both at baseline and following pharmacologically induced blood pressure increases and decreases in healthy volunteers [27]. Although this cheap noninvasive tool may be valuable in reconstructing blood pressure waveform, the theoretical background of suprasystolic wideband external pulse signals remains to be more extensively established.…”
Section: Miscellaneousmentioning
confidence: 94%